Headmaster’s Policies Pattern in the Learning Process at Covid 19 Pandemic Era (Case Study at SDN 28 Air Tawar Timur, Padang Utara Ditrict) - rosita, efiana (STAIN Madina Press, 2020)
Manage a school in a pandemic covid 19 is not a simple one by a headmaster. Need an adjustments from various aspects such as geographical conditions of the outbreak of covid 19, healthy lifestyle patterns of the school society, the availability of facilities provided by school if the learning process will do and others reason that make the learning process in this recent time is not simple. The unsimplicity is further complicated when we observed at elementary school as a lowest level with various students who have lack of understanding to information technology and a learning system. The emergence challenges that exist in the learning process of the covid 19 pandemic era need a headmaster who can finding many ideas and policies being opportunity for producing the creativity of the teachers, students, and parents. This research is a qualitative research with a case study approach. Data in this research was collected by observation, interview, and documentation study. Data were analyzed through three stages: data reduction, data presentation, and conclusion. Informant research are the headmaster, teachers, students, parents, and supervisor. The findings of this research are: 1) The policy pattern by headmaster at SDN 28 Air Tawar Timur based on democracy system, 2) The policy was made by headmaster for teachers, students, and parents, 3) The headmaster’s policies at SDN 28 Air Tawar Timur in the learning process and pandemic era giving impact for creativity of the teachers, students, and parents.